Improvement of lignocellulosic pretreatment efficiency by combined chemo - Mechanical pretreatment for energy consumption reduction and biofuel production. (January 2022) - Areepak, Chitchanok; Jiradechakorn, Thitirat; Chuetor, Santi; Phalakornkule, Chantaraporn; Sriariyanun, Malinee; Raita, Marisa; Champreda, Verawat; Laosiripojana, Navadol
Abstract: A pretreatment process is a preliminary stage to alter the recalcitrant structure of lignocellulosic biomass for enhancing its digestibility. An evaluation of the energy consumption and the environmental restrictions of the pretreatment step is required to develop a feasible eco-friendly process for industrial implementation. In this study, a combined alkaline-mechanical fractionation of rice straw for fermentable sugar (FS) production was developed with the objectives of i) evaluating energy efficiency and ii) addressing the sustainability of technology. The maximum fermentable sugar production was 0.54 kg/kg rice straw with an enzymatic hydrolysis efficiency of 97.34%. Furthermore, the results indicated that the pretreatment by 5% NaOH followed by mechanical size reduction provided the highest energy efficiency of 0.35 kg of FS/kWh with 94.44% glucose recovery, which also provided the lowest waste generation of less than 0.1 kg of waste/kg FS. These experimental results suggest that the combined alkaline-mechanical fractionation could effectively increase total FS yields and could be a promising pretreatment technology for an eco-friendly and sustainable pretreatment process integrated into a biorefinery platform. Graphical abstract: Image 1